(untitled) (Washington, DC, 2005)
With the knowledge of possible outcomes, what kind of actions should we take? The Millennium Ecosystem Assessment scored 74 response options for dealing with declines in ecosystem services and biodiversity, and managing drivers such as climate change and nutrient loading. This third volume in the MA series analyzes the track record of past policies and the potential of new ones.
Keywords: Human ecology,Sinh thái con người